An Analysis of Changing Character of ‘R’ Through Motivation Theory in the Movie Warm Bodies Directed by Jonathan Levine - Yunita; Irpan Ali Rahman (e-LinguaTera, 2023)
The purpose for the study is to obtain the information about how the motivation portrayed the main character in the movie “Warm Bodies”. Motivation is generally interpreted someone’s desire to achieve success in any case. In research, the writer uses the movie of “Warm Bodies” as the main material to analysis the data. The theories on literature are necessary to use in analyzing the character in order to answer the research question on chapter 1. The research finding that the main character has change from antagonist into protagonist because of motivation. R as zombie, he help a girl wanted to be human because he wanted to be with someone he loves, so he never gave up to take a chance. The writer analyzed the character of R, through motivation theory, R changes because of motivation.